Best of spirituals & gospels: fifty nine great songs easy arranged for piano, guitar, vocals (Editorial Schott, 2001)
In this volume, we hace put toguether fresh arrangements of the most beautiful Spirituals and Gospels. There are also some lesser-known "gems" for the discover.